Mamite bovina em rebanhos leiteiros da região sul do Estado de Minas Gerais - Geraldo Marcio da Costa (2008)
Etiological and epidemiological aspects of bovine mastitis were studied in 35 dairy herds of southern region of Minas Gerais state. High rates of mastitis associated with high somatic cell counts were observed in most herds studied. Contagious agents represented by coagulasepositive Staphylococcus (34.29%) and Streptococcus agalactiae (21.82%) were the predominant isolated microorganisms. Environmental agents accounted for 18.35% of the isolates, with Streptococcus uberis (6.52%), Enterobacteriaceae (3.64%) and yeasts (3.35%) as predominant pathogens. It was obtained low rates of isolation of yeasts and Candida was the main isolated genus. Environmental agents had greater participation in clinical cases in relation to contagious agents, exception to Streptococcus agalactiae. Antibiotic resistance, PCR-RFLPand sequencing tests aiming the study of the population diversity of Staphylococcus aureus were performed. These tests revealed the existence of a great diversity in population of and predominance of few clonal types in most studied herds. Sequencing of electrophoretic typesobtained in the PCR-RFLP confirmed the phylogenetic closeness among the isolates. There was no association of antibiogram or RFLP clonal types with mastitis forms. Failures on the main measures for mastitis control were observed in most analyzed herds, which justified thehigh occurrence of disease